Search method for an emission line of a GW background. (May 2016) - Nishizawa, Atsushi; Seto, Naoki
Abstract: A sharp emission line of a gravitational-wave background (GWB) would be an interesting observational target. Here we study an efficient method to detect a line GWB by correlating data of multiple GW detectors. We find that the width of frequency bin in the data analysis is a critical parameter, and, with the commonly-used value 0.25 Hz, the signal-to-noise ratio could be decreased by up to a factor of 6.6, compared with a finer width of 0.02Hz. By reanalyzing the existing data with a smaller bin width, we might detect a precious line signal from the early universe.